Publication ethics for researchers - Probir K. Banerjee (International Journal of Management, Economics and Social Sciences (IJMESS), 2013)
The community of researchers unanimously agrees that a code of ethics must be followed when engaging in research and consenting to publication of research findings in academic journals. However, unethical research practice continues to cause concern. In an effort to address the concern, several researchers have prescribed remedial action. Publishers and members of the research community have also tried to raise awareness of this malady plaguing the research community. For example, Ethics in Research & Publication, a website created by Elsevier, a trusted publisher of science and health information, aims to raise awareness in this regard by providing examples of scientific misconduct and breach of publications ethics, including plagiarism. Similarly, the iThenticate blog discusses plagiarism and other scholarly misconduct issues in a bid to promote integrity and ethical writing practices.
Keywords: 330